Konwersacja jako fenomen społeczny i jako przedmiot badań - Przywara, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The paper deals with the relationship between conversation and different contexts as well as constraints of research which appear within scientific disciplines analysing interpersonal communication, especially within pragmatics. It is pointed that the studies on conversation ought to be reinforced with an epistemological approach.
Conversation as a Social Phenomenon and Area of Scientific Research
Keywords: conversation; theory of conversation; contextuality; pragmatics